Defying gravity: defining the international rule of law - McCorquodale, Robert (Cambridge University Press, 2016)
This article aims to offer a definition of the international rule of law. It does this through clarifying the core objectives of a rule of law and examining whether the international system could include them. It demonstrates that there can be a definition of the international rule of law that can be applied to the international system. This definition of the international rule of law is not dependent on a simplistic application of a national rule of law, as it takes into account the significant differences between national and international legal systems. It seeks to show that the international rule of law is relative, rather than absolute, in its application, is not tied to the operation of the substance of international law itself, and it can apply to states, international organizations and non-state actors. It goes further to show that the international rule of law does exist and can be applied internationally, even if it is not yet fully actualized.